Six-Year Results From RELEVANCE: Lenalidomide Plus Rituximab (R2) Versus Rituximab-Chemotherapy Followed by Rituximab Maintenance in Untreated Advanced Follicular Lymphoma. Issue 28 (1st October 2022) - Morschhauser, Franck; Nastoupil, Loretta; Feugier, Pierre; Schiano de Colella, Jean-Marc; Tilly, Hervé; Palomba, Maria Lia; Bachy, Emmanuel; Fruchart, Christophe; Libby, Edward N.; Casasnovas, Rene-Olivier; Flinn, Ian W.; Haioun, Corinne; et al.
Abstract : Clinical trials frequently include multiple end points that mature at different times. The initial report, typically based on the primary end point, may be published when key planned co-primary or secondary analyses are not yet available. Clinical Trial Updates provide an opportunity to disseminate additional results from studies, published in JCO or elsewhere, for which the primary end point has already been reported. The RELEVANCE trial (ClinicalTrials.gov identifier: NCT01650701 ) showed that lenalidomide plus rituximab (R 2 ) provided similar efficacy to rituximab plus chemotherapy (R-chemo) in patients with advanced-stage, previously untreated follicular lymphoma (FL). We report the second interim analysis of the RELEVANCE trial after 6 years of follow-up. Patients with previously untreated grade 1-3a FL were assigned 1:1 to R 2 or R-chemo, followed by rituximab maintenance. Coprimary end points were complete response (confirmed/unconfirmed) at week 120 and progression-free survival (PFS). At median follow-up of 72 months, 6-year PFS was 60% and 59% for R 2 and R-chemo, respectively (hazard ratio = 1.03 [95% CI, 0.84 to 1.27]). Six-year overall survival was estimated to be 89% in both groups. Median PFS and overall survival were not reached in either group. Overall response after progression was 61% and 59%, and 5-year estimated survival rate after progression was 69% and 74% in the R 2 and R-chemo groups, respectively. The transformation rate per year in the R 2 and R-chemo groups was 0.68% and 0.45%, and secondary primary malignancies occurred in 11% and 13% ( P = .34), respectively. No new safety signals were observed. R 2 continues to demonstrate comparable, durable efficacy and safety versus R-chemo in previously untreated patients with FL and provides an acceptable chemo-free alternative.